The dragon's tooth [compact disc, unabridged] - Wilson, Nathan D. (Wilson, Nathan D. Ashtown burials, 2011)
When their parents' seedy old motel burns down on the same night they are visited by a strange man covered in skeleton tattoos, Cyrus, Antigone, and their brother Daniel are introduced to an ancient secret society, and discover that they have an important role in keeping it alive.